Sequence variation determining stereochemistry of a Δ11 desaturase active in moth sex pheromone biosynthesis. (July 2016) - Ding, Bao-Jian; Carraher, Colm; Löfstedt, Christer
Abstract: A Δ11 desaturase from the oblique banded leaf roller moth Choristoneura rosaceana takes the saturated myristic acid and produces a mixture of ( E )-11-tetradecenoate and ( Z )-11-tetradecenoate with an excess of the Z isomer (35:65). A desaturase from the spotted fireworm moth Choristoneura parallela also operates on myristic acid substrate but produces almost pure ( E )-11-tetradecenoate. The two desaturases share 92% amino acid identity and 97% amino acid similarity. There are 24 amino acids differing between these two desaturases. We constructed mutations at all of these positions to pinpoint the sites that determine the product stereochemistry. We demonstrated with a yeast functional assay that one amino acid at the cytosolic carboxyl terminus of the protein (258E) is critical for the Z activity of the C. rosaceana desaturase. Mutating the glutamic acid (E) into aspartic acid (D) transforms the C. rosaceana enzyme into a desaturase with C. parallela -like activity, whereas the reciprocal mutation of the C. parallela desaturase transformed it into an enzyme producing an intermediate 64:36 E/Z product ratio. We discuss the causal link between this amino acid change and the stereochemical properties of the desaturase and the role of desaturase mutations in pheromone evolution. Graphical abstract: Highlights: Sequence similarity between CroΔ11 and CpaE11 are very high although the catalytic output ( E/Z isomerism) is very different. Mutated versions of CroΔ11 were created, either containing one aa change or two neighboring aa changes. CroΔ11_E258D decreased the Z activity dramatically and the reciprocal mutation in CpaE11 bestows CpaE11 with Z activity.